TINDAK TUTUR ILOKUSI PEDAGANG KAKI LIMA PASAR PAGI KOTA PEMANGKAT: TINJAUAN PRAGMATIK - ramadhan, Wahyu; Syahrani, Agus; Muzammil, Ahmad Rabi’ul (Universitas Tanjungpura, 2024)
This research discusses speech acts or language use in the morning market street vendors of Pemangkat city, Sambas Regency. The purpose of this study is to describe the speech acts of Sambas language used by street vendors of Pemangkat city morning market using Pragmatics Review. The method used in this research is descriptive method in qualitative form. The source of data in this research is the morning market street vendors of Pemangkat city. Data collection techniques in this study used recording and note-taking techniques by means of field observation first then going down to the field, data collection, and documentation. This research produces illocutionary speech acts spoken by Pemangkat city morning market street vendors ranging from vegetable and meat traders. Based on the data analysis, the assertive speech acts in this study are 21 speech acts in Pasar Pagi Street Vendors consisting of stating, claiming, complaining, suggesting, boasting. Therefore, this assertive illocutionary speech act is more than other speech acts. Directive speech acts are found as many as 12 illocutionary speech acts consisting of begging, recommending, and ordering. Commissive speech acts were found as many as 5 speech acts, namely offering. Expressive speech acts are found as many as 11 speech acts consisting of thanking, praising, and apologizing. Furthermore, there are 6 declarative speech acts consisting of surrendering and ostracizing.